Vivências de formação crítica docente em um contexto de educação bilíngue de elite - Garcia, Ana Letícia Souza (2020)
In this study, I aim to discuss what meanings about critical language teaching and social class are built in a critical education work with six elementary school teachers in a prestigious bilingual education context. The empirical material was generated through initial interviews, reflective sessions, the researcher's diary and a final individual interview. The teachers participated in five reflective sessions, approximately 1h30min each, in the second semester of 2018, from October to December, in which academic praxiologies about bilingual education, critical language teaching and social class were problematized. In order to understand social class theoretically in the context of globalization and neoliberalism, I present several conceptions of social class, hierarchization and colonial difference, creating a social-historical overview based on Block, starting by Marx, Durkheim and Weber ideas, then Bourdieu, concluding with Mignolo’s decolonial perspective. In relation to the meanings constructed regarding critical language teaching and social class throughout the inquiry, I could notice that the action of reading theoretical articles and discussing them in the reflective sessions provided for most of the participants opportunities to expand their perspectives about critical language teaching. Throughout the final individual interview, they were able to elaborate and reframe their own praxiologies after the contact with academic praxiologies regarding critical teaching. In addition, reflections and problematization concerning social class and colonial differences provided opportunity for the group to discuss the complexity and fluidity of body classifications and hierarchizations, based on several elements such as material and symbolic capital, and they showed how students read and stereotype teachers’ social class. From the discussions, the participants also analyzed their own praxis and the students’ social and historical context in order to propose projects focusing on social class in their classrooms aiming at contributing to students’ understanding of their privilege position and to their awareness of social injustices.